EFFECT OF OWNERSHIP STRUCTURE FINANCIAL DISTRESS IN MINING COMPANY LISTED ON THE EFFECT OF OWNERSHIP STRUCTURE FINANCIAL DISTRESS IN MINING COMPANY LISTED ON THE EFFECT OF OWNERSHIP STRUCTURE FINANCIAL DISTRESS IN THE MINING COMPANY REGISTERED IN IDX - Agus Rinaldi; Haryetti '; Ahmad Fauzan Fathoni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was conducted on mining companies listed on the Indonesia Stock Exchange with years of research from 2009 to 2012. The data required in this study were obtained by means of the research literature-literature published by the Indonesia Stock Exchange, namely Indonesian Capital Directory (ICMD) issued by the Economic and Financial Instute for using secondary data to collect data in the form of documentation, archives and other data which supports research related to the study variables. The purpose of this study is to provide empirical evidence about the effect of managerial ownership on financial distress, to provide empirical evidence on the effect of institutional ownership on financial distress, to provide empirical evidence about the influence of foreign ownership of financial distress. Based on the results of the study indicate that there is no influence of managerial ownership with financial distress on mining companies listed on the Indonesia Stock Exchange, there are significant institutional ownership with financial distress on mining companies listed on the Indonesia Stock Exchange, there is no influence of foreign ownership in financial distress at the company mining listed in Indonesia Stock Exchange. Limitations of the research in this study to determine the effect of managerial ownership, institutional ownership and foreign ownership of financial distress. The object of research is a mining company listed on the Indonesia Stock Exchange 2009-2012. Advice can be given is to the Capital Market Supervisory Agency (Bapepam) and the Indonesia Stock Exchange, oversight of ownership in each company to be made more strict and firm, and establishes rules regarding the ownership of the share capital. And expected to be able to measure the factors that cause financial distress at the company in addition to the variables that I researched.Keywords : Managerial Ownership, Institutional Ownership, Foreign Ownership, Financial Distress.